Welfare Initiatives and their Roles on Job Stability of Catering Employees in Selected Universities in Nairobi City County, Kenya. - Waweru, Bernard K.; Maranga, V.N.; Mugambi, R. (Machakos University, 2019)
The study sought to establish welfare initiatives and their roles on job stability of catering employees in selected universities in Nairobi City County, Kenya. The study covered aspects of efforts, programs, services, benefits and facilities provided by the universities to their catering employees. The study also covered the aspects of concerned with roles of welfare initiatives on job stability such as; employee’s sense of being valued, employees’ attachment, improved performance, fringe benefits, employees’ commitment, talents retention, hard work, competency, a sense of ownership, employees loyalty, employees satisfaction and a sense of fulfillment. The study was descriptive covering a stratified sample of 189 respondents drawn from 300 employees. Data was collected through self-administered questionnaires and an interview guide questions. The respondents agreed with the provision of uniforms, medical facilities, clean safe working station and employee’s assistance with means of between 1.5 to 2.5. However, with a mean of between 3.5 to 4.5, they strongly disagreed that, they are provided with welfare initiatives; meals allowance, long service grants, paid holidays and recreational facilities. Moreover, with a mean of 2.57, the respondents were neutral with the provision of; sufficient number of toilets (2.57) and housing facilities. The results of standard deviations were as follows; leave policy (1.53), sporting facilities(1.24), regular salary increment (1.37), comprehensive pension policy (1.35), sufficient number of toilets (1.08), meals allowance (1.25), long service grants (1.15), canteen facilities (1.04), counseling service (1.12), paid holidays (1.30), recreational facilities (1.09), well maintained restrooms (1.13), medical facilities (1.02), employee’s funeral assistance (1.32) and transfer assistance (1.37) had a standard deviation >1, implying that, there was a significance variance. Housing facilities (0.99), uniforms (1.00) and a clean station (0.94), had a standard deviation <1, meaning, there was no significance variance and hence consensus in responses. With a mean of 1.86 and a standard deviation of .979, majority agreed that welfare initiatives make them feel valued by their universities. 86.2% agreed that, being valued makes them more attached to their universities. A mean of 1.84 and a standard deviation of .839 revealed that, welfare inspires employees to work hard and better. It is evidenced with a mean of 1.82 and a standard deviation of .921 that, fringe benefits enhances employee’s commitment. A mean of 2.50 and a standard deviation of 1.483 revealed a concurrence that, welfare initiatives attracts and retains talents of university catering departments. A majority of respondents 42.8% were of the opinion that, welfare initiatives inspires hard work and competency among the university catering employees. A mean of 2.39 and a standard deviation of 1.557, the respondents opined that, welfare initiatives enhance their satisfaction levels. Moreover, with a mean of 1.39 and a standard deviation of .769, the respondents were of the view that, welfare initiatives allows them to take pride in their organizational membership. A majority of the respondents (86.8%) held that, welfare initiatives allow employees loyalty. It is evidenced with a mean of 1.93 and a standard deviation of .716 that, welfare initiatives enables employees to work with passion and fulfillment. The findings demonstrated with a mean of 1.81 and a standard deviation of 0.820 that, welfare initiatives enables employees to continue working with their organizations
Keywords: Welfare Initiatives; Welfare Services; Welfare Benefits; Employees’ attachment; Employees loyalty; Employees satisfaction; Psychological contract; Employees fulfillment.